The role of indigenous lactic acid Bacteria Genus Lactobacillus in the fermentation process of Durian (Durio zibethinus) for Tempoyak production - Yunita Ayu Ardilla; Krisna Wahyu Anggreini; Tara Puri Ducha Rahmani (Berkala Ilmiah Biologi, 2022)
Durian (Durio zibethinus) is a type of fruit included in the climacteric fruit, so it needs processing to have a longer shelf life. One of the processed durian fruits is tempoyak. Tempoyak is a traditional fermented durian food well known around Kalimantan and Sumatra. Tempoyak is made from durian, which usually has a good level of maturity. The distinctive aroma and semi-solid texture of tempoyak are produced by the fermentation process by bacteria. Tempoyak processing has involved adding a bit of salt and indigenous lactic acid bacteria, one of which is the bacteria genus Lactobacillus, such as Lactobacillus plantarum and Lactobacillus curvatus. This study aimed to determine the role of lactic acid bacteria from the genus Lactobacillus in the fermentation process of durian into tempoyak, to determine the potential of bacteria from the genus Lactobacillus in other respects, and to determine the health benefits of tempoyak. This research was conducted using a literature study method with several stages, namely article searching, article selection, data synthesis, and ending with report generation. From the literature search, it can be seen that indigenous bacteria from the genus Lactobacillus are found in fermented durian fruit. Lactobacillus plantarum and Lactobacillus curvatus are species of the genus Lactobacillus that can ferment sugar into lactic acid and are usually used in fermented agricultural products and livestock products. Lactobacillus plantarum producing lactic acid is amylolytic because it can directly convert starch to form lactic acid. Lactobacillus curvatus has various functions related to carbohydrate utilization and bacteriocin production, enabling fermentative and antibacterial properties. Tempoyak can be beneficial for digestive health and has the potential to increase the body's immune system. The results obtained prove that the indigenous bacteria of the genus Lactobacillus from tempoyak play a role in the durian fermentation process and have the potential as probiotics that are good for health.